Provenance and uranium source of the lower cretaceous sedimentary rocks in Northern Sichuan Basin: evidence from sedimentary facies analysis and detrital zircon U-Pb geochronology - Wen-hao Li; De-ru Xu; Jia-bao Yang; Qiu-shuang Fan; Zhao-kun Yan; Cheng-yong Zhang; Zeng-hua Li (Journal of Asian Earth Sciences: X)
In this paper, we present results of sedimentary facies analysis and U-Pb dating of detrital zircons from the Lower Cretaceous uranium-bearing sandstones in northern Sichuan Basin, to investigate the influence of provenance and sedimentation process on the temporal and spatial distribution of uranium-bearing sandstones. The results show that there are four major zircon U-Pb age populations that cluster at 2800–2200 Ma (group 1), 2200–1600 Ma (group 2), 1600–538 Ma (group 3), and 538–145 Ma (group 4), respectively. The age data, combined with regional tectonic events, indicate that zircons of group 1, group 2 and group 3 in the western part of the Sichuan basin were mainly derived from the Bikou and Songpan-Ganzi terranes, and the varieties of group 4 were mainly originated from the Longmenshan thrust belt. Whereas zircons of group 1, group 2 and group 3 in the eastern part of the Sichuan basin were primarily sourced from the South Qinling Belt and the Bikou terrane, and those of group 4 were likely affiliated with the Hannan Micangshan massif and Dabashan thrust belt. The Paleozoic low-grade metamorphic rocks and Mesozoic sedimentary rocks and minor intermediate-acidic magmatic and volcanic rocks represented by group 4 zircons are considered as the primary source for uranium mineralization in the Lower Cretaceous sandstones. The Neoarchean to Proterozoic metamorphic rocks and plutonic and volcanic rocks, as revealed from the group 1, group 2 and group 3 zircons also contributed partially to the uranium sources.